Engineering a Blood‐Retinal Barrier With Human Embryonic Stem Cell‐Derived Retinal Pigment Epithelium: Transcriptome and Functional Analysis. (3rd June 2013) - Peng, Shaomin; Gan, Geliang; Qiu, Caihong; Zhong, Mei; An, Hongyan; Adelman, Ron A.; Rizzolo, Lawrence J.
Abstract : To develop a culture model for drug development and tissue‐engineering human retina, retinal pigment epithelia (RPE) were derived from human embryonic stem cells (hESCs), and their barrier properties were compared with those of a well‐regarded model of RPE function, human fetal RPE isolated from 16‐week‐gestation fetuses (hfRPE). It was found that hESC‐derived RPE is highly differentiated but may be less mature than RPE isolated from 16‐week fetuses. The study also identified a panel of genes to monitor further maturation of RPE. Abstract : Retinal degenerations are a major cause of impaired vision in the elderly. Degenerations originate in either photoreceptors or the retinal pigment epithelium (RPE). RPE forms the outer blood‐retinal barrier and functions intimately with photoreceptors. Animal models and cultures of RPE are commonly used to screen potential pharmaceuticals or explore RPE replacement therapy, but human RPE differs from that of other species. Human RPE forms a barrier using tight junctions composed of a unique set of claudins, proteins that determine the permeability and selectivity of tight junctions. Human adult RPE fails to replicate these properties in vitro. To develop a culture model for drug development and tissue‐engineering human retina, RPE were derived from human embryonic stem cells (hESCs). Barrier properties of RPE derived from the H1 and H9 hESC lines were compared with a well‐regarded model of RPE function, human fetal RPE isolated from 16‐week‐gestation fetuses (hfRPE). A serum‐free medium (SFM‐1) that enhanced the redifferentiation of hfRPE in culture also furthered the maturation of hESC‐derived RPE. In SFM‐1, the composition, selectivity, and permeability of tight junctions were similar to those of hfRPE. Comparison of the transcriptomes by RNA sequencing and quantitative reverse transcription‐polymerase chain reaction revealed a high correlation between the hESCs and hfRPE, but there were notable differences in the expression of adhesion junction and membrane transport genes. These data indicated that hESC‐derived RPE is highly differentiated but may be less mature than RPE isolated from 16‐week fetuses. The study identified a panel of genes to monitor the maturation of RPE.